PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR NPK DENGAN TEKNOLOGI MNBS (MICRO NANO BUBBLES) - Naldi, Henra; Vauzia, Vauzia; Chatri, Moralita; Sholichin, Muhamad (Jurnal Pengabdian Masyarakat Sabangka, 2022)
Policy reforms and research on agricultural ecology need to be intensified to reduce land damage and the massive ecological and chemical impacts of soil pollution. This is related to the increasing population that requires clothing, food and welfare. Furthermore, although there has been a shift towards a form of agriculture with high added value. This problem must be found a solution by diversifying efforts, ecological applications on agricultural cultivation land and making breakthroughs in making organic fertilizers with various sources and environmentally friendly ways. This is rational and can be done by involving the industry, universities and farmer groups who are smart and productive. The results of community service as many as 34 respondents were interested in making NPK liquid fertilizer.   Keywords:  NPK Liquid Fertilizer, MNBs, Community Service